Organizational crisis and sensemaking: the case of a public hospital within the context of the influenza A (H1N1) pandemic - Eberle, André Davi (2012)
This research is a case study in which an organizational crisis that occurred in a large public hospital within the context of the influenza A (H1N1) pandemic of 2009 was analyzed. This research aimed to analyze the process of organizational crisis, taking into account the sensemaking processes carried out by hospital professionals during the crisis. The theoretical framework was constructed with the themes of organizational crisis and sensemaking as a basis. Data collection was achieved through semi-structured individual interviews, focus groups, and documentary analysis. Content analysis was then carried out. The analysis of the organizational crisis process which occurred in the hospital was performed according to the characterization of the following periods: (I) the period prior to the crisis disruption, when warning and vulnerability signs were observed; (II) the disruptive moment, related to the occurrence of the event triggering the crisis; (III) the acute crisis phase. Our results indicated that the sensemaking processes performed by professionals influence how they acted during the organizational crisis.